Scope of using ICT for knowledge management on adaptation to climate change in agriculture (International Journal of Agricultural Research, Innovation and Technology, 2021)
The char land of Bangladesh is vulnerable to climate change. There are changes in extreme weather events. Impact of climate change resulted feminization of agricultural practices. Number of development interventions have been taken to skill the rural community to take adaptation action on agriculture. Development interventions taken in the char land of Dimla, Nilphamari were studied from June 2018 to December 2019 to identify the capacity of climate change adaptation interventions using the information and communication technology to empower women. Mobile Phone Use Index study found that nearly three-fourth of rural female farmers were capable to manage knowledge on climate change adaptation if their access to device was ensured. Inclusion of women in the technology playing a very important role towards transformative leadership. Nearly 85% of the women farmers have high environmental awareness; likely to be contributory to adaptation knowledge management. Community themselves identified them more resilient comparing with areas where promotion of technology is not supported. Institutes with the capacity of information technology promotion could be the hub of resilience knowledge management for women, but external supports are required there. Self-motivation supported by project intervention has created notable capacity of a good number of women who could be the mentor of women transformative leadership towards resilience.Int. J. Agril. Res. Innov. Tech. 10(2): 1-6, December 2020